LEVEL OF ACCEPTANCE OF INFORMATION TECHNOLOGY BY RURAL PRODUCERS - Cunha, A. C.; Putti, F. F. [UNESP] (Universidade Estadual Paulista - Campus de Tupa, 2020)
Information Technology has played a fundamental role in the most diverse professional sectors, including in the agricultural sectors, providing facilities in the processes, data storage, reports of various types and also through the Internet, consultations and acquisition of knowledge. However, the adoption of Information Technology by rural producers is not always done, even with the advantages it provides. In this context, the objective of this article was to analyze the level of acceptance of information technology by rural producers in some cities in the southern region of Minas Gerais. For that, a data survey was carried out through a questionnaire with 18 questions that was applied with 44 rural producers. Through the questionnaires applied, it was possible to verify that many farmers have access to the Internet and devices such as computers. However, they still have some resistance regarding the adoption of Information Technology, even though it should be borne in mind that such technology could assist them in their production processes.
NÍVEL DE ACEITAÇÃO DA TECNOLOGIA DA INFORMAÇÃO POR PRODUTORES RURAIS
Keywords: agriculture; computing; internet; software; technology